The 'ghost of past fishing': Small-scale fisheries and conservation of threatened groupers in subtropical islands. (January 2017) - Silvano, Renato A.M.; Nora, Vinícius; Andreoli, Tainá B.; Lopes, Priscila F.M.; Begossi, Alpina
Abstract: Groupers are highly targeted and vulnerable reef fishes. The effects of fishing pressure on the density of three reef fishes were investigated in 21 islands outside (n=15) and inside (n=6) a Marine Protected Area (MPA) at the Paraty Bay, Brazilian southeastern coast. Two valued groupers ( Epinephelus marginatus and Mycteroperca acutirostris ) and a non-target grunt ( Haemulon aurolineatum ) were studied. The total biomass of fish caught in each island was considered as a measure of current fishing pressure, while the island distance from the villages was considered as a measure of past fishing pressure. Fish densities were recordedin number and biomass. The biomass of M. acutirostris was inversely related to current fishing pressure, which did not affect the other two fishes. The density of E. marginatus increased with the island distance from one of the fishing villages, which indicated that past fishing may have had decreased the abundance of E. marginatus . Densities of the three fishes and fishing pressure did not differ between islands inside and outside the MPA. Data on fishing pressure, densities of groupers and coral cover were combined here to assign conservation scores to islands. A redefinition of MPA boundaries to reconcile fish conservation, fishing activities and fishers' food security was proposed. Highlights: Effects of fishing pressure on the density of three reef fishes were investigated. 21 islands were studied outside and inside a Brazilian Marine Protected Area (MPA). Biomass of one grouper was inversely related to biomass of catches (current fishing). Density of other grouper increased with island distance from village (past fishing). Densities of the three fishes and fishing pressure were unrelated to the MPA.